Advertising in the Age of Disinformation: Influencers and Natural Contraception - Westwood, Hannah L. (AoIR Selected Papers of Internet Research, 2026)
This paper discusses health disinformation, focusing on the example of disinformation about contraception on social media, to understand the context within which alternative contraceptives like $2 are advertised. $2 is a digital contraceptive app that uses body temperature data to predict and confirm ovulation in order to confirm fertility status. It has grown in popularity on social media alongside the increase in contraceptive disinformation. The paper presents a discussion of the context of disinformation along with a close reading of the visual and textual elements of the $2 influencer advertisements, drawing on work on influencers, platform economies and authenticity to show how lived experiences are co-opted for commercial purposes to promote products like $2 . I find that the context of contraceptive disinformation feeds into wider wellness and right-wing ‘tradwife’ trends, which are evoked by the influencer advertisements studied. As such, I contend that while $2 influencer advertisements do not directly contain disinformation, the techniques employed evoke similar messages as the trends that do contain disinformation. In so doing, the advertisements co-opt influencers’ lived experiences to present $2 as a superior alternative to hormonal contraception. Thus, $2 effectively promotes its product while avoiding the criticism levelled at contraceptive disinformation.